PROCUREMENT BUSINESS PROCESS REENGINEERING IN MANUFACTURING COMPANIES USING BUSINESS PROCESS ANALYSIS METHODS - Fitria, Fitria; Feta, Neneng Rachmalia; Satria, Deki (Jurnal Pilar Nusa Mandiri, 2022)
The high Increas business competition makes many organizations in any field to be able to run their business more quickly and effectively to achieve business goals. Business processes are a series of activities carried out by organizations to achieve organizational goals, in manufacturing companies the procurement business process is one of the main business processes of the organization. Therefore, in this study, an analysis of the procurement business process was carried out and then designed a more optimal targeting business process engineering for the organization. Business process engineering is carried out by analyzing business processes using the valued added analysis, flow analysis and simulation methods. The results of business process engineering show that targeting business processes that are prepared are better in terms of time and costs compared to existing business processes.